Conceptual Change in the History of the Humanities - Solleveld, Floris (Studium, 2015)
Was there ever a ‘scientific revolution’ in the Humanities, and to what extent is that notion applicable to the Humanities at all? In this article, I formulate various ways in which to answer that question. These options emerge from a discussion of what I identify as the ‘Standard Account’ of developments in the Humanities around 1800, the essentials of which are in the work of Michel Foucault, Hans-Georg Gadamer, and Isaiah Berlin. Without calling it as such, the Standard Account amounts to a description of a scientific revolution. However, this Account works as a model and a set of tacit assumptions rather than as an explicit article of faith, and all of its tenets have been criticized. Making its assumptions and shortcomings explicit leaves one with four alternatives: 1. in spite of all shortcomings and criticism, the Standard Account is largely correct; 2. there was a revolution, but it was different; 3. there were various breakthroughs and more or less revolutionary events rather than one revolution; or 4. there was no revolution in the Humanities at all. Evaluating these alternatives also throws a new light on the dynamics of conceptual change – how the humanities bring forth new ideas.